Rupture of the rudimentary uterine horn during pregnancy: a clinical case - Valeriia Shatokhina; Nataliia Skuriatina (Bogomolets National Medical University, 2022)
this article describes a clinical case of a ruptured rudimentary uterine horn during pregnancy. Difficulties in timely diagnosis of pregnancy in a rudimentary uterine horn can result in urgent surgical intervention for uterine horn rupture and antenatal fetal death, increased frequency of obstetric bleeding, hemorrhagic shock, and increased frequency of hemotransfusions. The aim of this study was to demonstrate the variant of recurrent pregnancy, which was developed in a non-communicating rudimentary horn of a unicornuate uterus. The materials of the study was data of medical history, which included anamnestic data, results of laboratory and instrumental studies, surgical protocol, and epicrisis. A 16-weeks pregnant woman was admitted to the emergency department of the maternity hospital in an extremely severe condition with signs of acute intraabdominal hemorrhage in 2020. According the situation, an urgent lower midline laparotomy and abdominal cavity revision were performed. An abnormality of the development of the uterus was revealed during the operation - a one-horned uterus with a contralateral rudimentary horn not connected to the uterine cavity and with signs of an interrupted pregnancy due to a rupture of the horn. Tactics of operative treatment included rudimentary horn's resection, complete hemostasis, sanation and drainage of the abdominal cavity. Also, an intensive therapy was performed, which included transfusion of fresh frozen plasma and red cell mass. The systematization of literary sources on the issues of congenital anomalies of the uterus showed a high risk of pregnancy development in the rudimentary horn of the uterus and a high frequency of complications of this pregnancy in the form of horn rupture, mainly in the second trimester. The systematization of approaches to solving the problem of rudimentary horn rupture during pregnancy shows that a higher priority is given to the tactics of preserving a normally developed horn with infusion therapy in the management of patients with rupture of the rudimentary horn of the uterus and relatively unstable hemodynamics. At the same time, a discussion of successful cases of planned rudimentary horn's resection with the fetus and normal recurrent pregnancy is demonstrated. The results of this clinical case may be useful for obstetricians, general surgeons, and ultrasound diagnostic specialists to improve the detection of rare anomalies of the female reproductive system in differential diagnosis of "acute abdomen" causes in women and optimize surgical tactics for the treatment of pregnancy complications in the rudimentary uterine horn.